New dimensions of learning space: immersive trainnig systems - Silva, P.N. Moreira da (2018)
The immersive training systems and virtual reality represent the new generation of learning spaces. This new computer technology has an incredible potential in education field. Virtual Training, Interface Checking, Full Digital Immersion are same the uncountable applications of those technologies. This paper provides an introduction to the new dimensions of learning spaces using virtual reality (VR) and its possibilities for learning space. Provides a brief overview of existent immersive training systems and show the potential for education and training in: (i) exploration; (ii) Training practical / technical skills; (iii) operation / maintenance; and (iv) academic concerns. Educational institutions will benefit from better accessibility to virtual technologies; this will make it possible to teach in virtual environments that are impossible to visualize in physical classrooms, like accessing into a mine. This type of visits may be conditioned due to difficult accesses, safety conditions and reduced space. The huge possibilities of accessible virtual technologies will make it possible to break the boundaries of formal education. This paper also aims to explore immersive virtual reality as a potential strategy for students learn about Geology and Geomining Heritage, addressing several topics, such as landscapes, rocks, ores, veins, exploitation and transformation processes and intangible heritage. An immersive learning experience is now being developed for the Naturtejo Geopark Interpretative Center.